Surgical treatment and outcome of sterile prostatic cysts in dogs. Issue 5 (7th May 2021) - Del Magno, Sara; Pisani, Guido; Dondi, Francesco; Cinti, Filippo; Morello, Emanuela; Martano, Marina; Foglia, Armando; Giacobino, Davide; Buracco, Paolo
Abstract: Objective: To describe the surgical treatment and outcome of a large cohort of dogs with sterile prostatic cysts (PCs). Study Design: Retrospective study. Animals: Forty‐four client‐owned dogs. Methods: Dogs with sterile PCs with at least 6 months of follow‐up were included. Clinical variables, type of surgery, complications, recurrences, and outcomes (telephonic interviews or rechecks) were recorded. Results: Extra‐ and intraparenchymal cysts were diagnosed in 29 and 11 dogs, respectively. Four dogs had both types. Extraparenchymal cysts were treated by partial resection and omentalization ( n = 22) and complete resection ( n = 7). Drainage and intracapsular omentalization were performed in all dogs with intraparenchymal cysts. The four dogs with both types of cyst were treated by omentalization. Resolution was documented in 39/44 dogs (88.6%). Intraoperative complications occurred in one dog (urethral tear). Major complications resulting in death occurred in three dogs (oliguric kidney injury, cardiac arrhythmia, and persisting urinary tract obstruction). Minor complications ( n = 10) consisted of temporary urinary incontinence ( n = 2), permanent urinary incontinence ( n = 5), urinary retention ( n = 2), and dysuria ( n = 1). Recurrence occurred in two dogs with extraparenchymal cysts. Median long‐term follow‐up was 528 days (range, 250–730 days). Thirty‐nine dogs had no signs associated with prostatic disease at long‐term follow‐up. Conclusion: Partial or complete resection and/or omentalization of sterile PCs led to resolution of clinical signs in most dogs, although postoperative urinary incontinence was frequent. Impact: This study is the largest case series relative to canine sterile PCs treated surgically and provides evidence on the prognosis and rate of complications.